Legume Lectin FRIL Preserves Neural Progenitor Cells in Suspension Culture In Vitro - Hailei Yao; Xiaoyan Xie; Yanhua Li; Dongmei Wang; Shu Han; Shuangshuang Shi; Xue Nan; Cixian Bai; Yunfang Wang; Xuetao Pei (Clinical and Developmental Immunology)
In vitro maintenance of stem cells is crucial for many clinical applications. Stem cell preservation factor FRIL (Flt3 receptor-interacting lectin) is a plant lectin extracted from Dolichos Lablab and has been found preserve hematopoietic stem cells in vitro for a month in our previous studies. To investigate whether FRIL can preserve neural progenitor cells (NPCs), it was supplemented into serum-free suspension culture media. FRIL made NPC grow slowly, induced cell adhesion, and delayed neurospheres formation. However, FRIL did not initiate NPC differentiation according to immunofluorescence and semiquantitive RT-PCR results. In conclusion, FRIL could also preserve neural progenitor cells in vitro by inhibiting both cell proliferation and differentiation.